SISTEM INFORMASI REKAPITULASI NILAI RAPORT SISWA SMP NEGERI 1 ASEMBAGUS - Supriyadi (Department of Science and Technology Ibrahimy University, 2018)
Academic activities in SMP Negeri 1 Asembagus take place every year. The number of new students who enroll in these institutions each year, requiring adequate service quality. Therefore, it needs an application that can help maximize the quality of existing services in SMP Negeri 1 Asembagus. This study has formulated the problem of how to make a recapitulation of the value of the student information system that can process a student's academic value quickly and accurate. Recapitulation of the value of the student information system will be built within the scope of academic only, not for others. This Research was conducted using the method of literature, interviews, observation, field research, and internet searching. From the explanation and the results of the discussion above, it can be concluded that the Summary of Information Systems Student Value At SMPN 1 Asembagus by using JAVA and MySQL can be used as a tool to help and make it easier for the school to cultivate students' grade reports.